Effect of Anterior Cervical Decompression Fusion and Partial Resection of Uncinate Vertebra Joint on Cervical Sagittal Sequence in Patients with Non‐Single‐Segment Radiculopathy and its Correlation with Curative Effect: A Retrospective Analysis. Issue 4 (7th February 2023) - Zhu, Jieyang; Feng, Dapeng; Song, Dehui; Dai, Zhong; Chen, Yaoning; Yan, Xiaobing; Li, Zhengwei
Abstract : Objective: Analyze the effect of preservation or resection of the partial uncinate joint on the sagittal sequence of the cervical vertebrae in patients with non‐single‐segment radiculopathy and the correlation between the sagittal sequence of the cervical vertebrae and the long‐term effect after surgery, we explored whether it is necessary to perform partial resection of the uncinate joint in patients with cervical spondylotic radiculopathy undergoing anterior cervical decompression and fusion (ACDF). Methods: The study retrospectively analyzed 96 patients with cervical spondylotic radiculopathy with more than two segments from August 2016 to January 2021, who underwent ACDF (ACDF group, 45 patients) or ACDF combined with partial uncinate joint resection (ACDF + UT group, 51 patients). Partial resection of the uncinate joint indicated removal of part of the uncinate joint and osteophyte based on the compression of the nerve root during surgery, whereas the uncinate joints in the ACDF group were retained completely. The imaging data and functional scores of the two groups were recorded before surgery, 1 month after surgery, and at the last follow‐up. A paired t‐test or rank sum test was applied to analyze the data. In addition, the correlation between the imaging parameters and functional scores was validated using the Pearson's test. Results: All 96 patients successfully completed the surgery and were followed up for at least 12 months, with an average follow‐up time of 14 months. At the last follow‐up, the pain visual analog scale (VAS), neck disability index (NDI), and neck pain and disability scale (NPAD) scores of the two groups were significantly lower than those before surgery, and the Japanese Orthopaedic Association (JOA) score was significantly higher than that before surgery. At the last follow‐up, compared with the ACDF+UT group, the NDI and NPAD scores in the ACDF group decreased more significantly (p < 0.05), and C2‐7SVA, △C2‐7SVA (the difference between C2‐7 SVA at last follow‐up and before operation), and T1S values decreased significantly (p < 0.05). The C2‐7 Cobb angle was positively correlated with the JOA score and T1S (p < 0.05) and negatively correlated with the VAS, NDI, and NPAD scores and CGH‐C7SVA (p < 0.05). C2‐7SVA was positively correlated with CGH‐C7SVA and T1S (p < 0.05). Conclusion: Patients with non‐single‐segmental cervical spondylotic radiculopathy and ACDF with or without uncinate joint resection can have effective improvement in the clinical effect and sagittal balance; however, partial uncinate joint resection has a certain negative impact on the long‐term reconstruction of sagittal balance and long‐term effects in patients after surgery. Abstract : ACDF retention or partial resection of uncinate joint can achieve a good therapeutic effect in the treatment of cervical spondylotic radiculopathy, but for the reconstruction and maintenance of sagittal parameters, the effect of preserving uncinate joint is better.